Chitosan-propolis combination inhibits anthracnose in 'Hass' avocados - Junior, A.K. Marino, José S.P.; Magalhães, Kelly M.; Mattiuz, Ben-Hur (Emirates Journal of Food and Agriculture, 2018)
The effect of chitosan-propolis combination on the control of in vitro and in vivo growth of Colletotrichum gloeosporioides, a causal agent of anthracnose, as well as on the quality of avocado of Hass cultivar has been evaluated. Chitosan and propolis were added to the culture medium separately and in combinations to verify the efficacy of inhibition of C. gloeosporioides mycelium in vitro. Avocados were immersed for 1 minute in the treatments that best inhibited the mycelium growth (in vitro) with the aim of testing the fungus control in vivo. The tested treatments were 1.5% chitosan and combinations of propolis (1.0%, 1.5%, 2.0%) with 1.5% chitosan and then inoculated with C. gloeosporioides. Control fruits were dipped in distilled water only. In the second experiment, avocados were immersed for 1 minute in the treatments that best inhibited the mycelium growth (in vivo) with the aim of testing the fruits quality. The tested treatments were 1.5% chitosan isolated and in the combination of 1.5% chitosan with 1.5% propolis. The control treatment were immersed only in distilled water. Avocados were stored at 22 ± 0.3 °C and 90 ± 3% RH for 7 days. The use of 1.5% chitosan in combination with 2.0% propolis controlled the mycelial growth of Colletotrichum gloeosporioides in vitro. In addition, coating with only 1.5% chitosan provided the best results in avocados, reducing the severity and incidence of anthracnose and maintaining the fruit quality.